Kepatuhan Melakukan Pengobatan Rutin Pasien Hipertensi Lansia pada Pandemi Covid-19 - Wardani, Novia Tri; Azinar, Muhammad (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Hypertension is a non-communicable disease that can be caused by many factors. Hypertension cannot be cured, but can only be controlled to reduce the risk of complications. Therefore, adherence to treatment is needed to prevent adverse effects on health. Puskesmas Pakis is the health center with the lowest coverage of hypertension services in Magelang Regency, which is only 0.6%. Methods: This type of research is analytic observational with a cross sectional research design. The total population in this study was 591. The number of samples was 90 respondents who were taken by purposive sampling technique. Measuring adherence to treatment using the MMAS (Modified Morisky Adherence Scale) questionnaire. Results: The results showed that the variables of JKN ownership (0.046), knowledge (0.003), family support (0.037), perception of vulnerability (0.000), perception of seriousness (0.000), perceived benefits (0.006), and perceptions of cues to action (0.009) related adherence treatment for elderly hypertensive patients in Puskesmas Pakis. Meanwhile, the variables of gender, employment status, duration of treatment, the role of health workers, and perceived barriers were not related to adherence treatment for elderly hypertensive patients in Puskesmas Pakis (p > 0.05). Conclusion: There is a relationship between JKN ownership, knowledge, family support, perceptions of vulnerability, seriousness, benefits, and cues to action with adherence treatment for elderly hypertensive patients.